1996
DOI: 10.1200/jco.1996.14.5.1552
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of intravenous topotecan as a 5-day infusion for refractory epithelial ovarian carcinoma.

Abstract: Topotecan shows modest clinical activity against cisplatin-refractory ovarian cancer, although the dose-intensity is compromised by the depth of the granulocyte nadir and the duration of granulocytopenia. Further studies of topotecan may necessitate a reevaluation of optimal dose schedule, with the possible incorporation of multilineage cytokines, and its activity in taxane-resistant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
1
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(115 citation statements)
references
References 9 publications
2
106
1
6
Order By: Relevance
“…No correlation between glomerular filtration rate or bilirubin level and hematological toxicity or response was reported. 18 Similarities were observed in this study (Table 4).…”
Section: Topotecansupporting
confidence: 88%
See 1 more Smart Citation
“…No correlation between glomerular filtration rate or bilirubin level and hematological toxicity or response was reported. 18 Similarities were observed in this study (Table 4).…”
Section: Topotecansupporting
confidence: 88%
“…17,27,29 The median durations for grades 3 and 4 neutropenia and thrombocytopenia were 10 and 5 days, respectively. 18 Maculopapular pruritic exanthema occurred in 20% of patients. Gastrointestinal side effects were mild.…”
Section: Topotecanmentioning
confidence: 99%
“…Three noncomparative phase II studies were conducted in patients with epithelial ovarian cancer (studies 012 [12], 033 [1], and 034 [4]) and three were conducted in patients with SCLC (studies 014 [6], 053 [14], and 092 [5]). A randomized, controlled, phase III study (study 039) [9,13] …”
Section: Pooled Studiesmentioning
confidence: 99%
“…Data from phase II trials showed that topotecan has efficacy in both platinum-sensitive and platinum-resistant ovarian cancer [5][6][7][8][9][10][11]. Based on these studies, a 30-minute i.v.…”
Section: Introductionmentioning
confidence: 99%